Olympia, Griechenland. Impressionen von Olympia während der Besatzungszeit, 1941– 1944 - Kankeleit, Alexandra (e-Forschungsberichte des DAI, 2019)
In July 2016 the project “Reappraising the History of the DAI Athens during the National Socialist Era” began. At the end of the project, the research findings are due to be presented in a monograph. Since then, there have been regular progress reports in the form of talks and essays on specific themes and questions. The research in both German and Greek archives offers insight into an historical epoch from which we are now divided by over two generations. The focus is on concrete events and activities, but also personal feelings and experiences which can provide information about the role of the German Archaeological Institute in Athens.